The Role of Market Orientation And Product Quality On The Performance of Small-Medium Enterprises With Supply Chain Management Strategies As Mediation Variables (Case Study On Songket Smes In Palembang City) - Chandra Satria; Antoni Antoni; Doly Nofiansyah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2022)
The purpose of this research was to analyze and measure the role of market orientation, product quality, supply chain management strategies as mediating variables on the performance of small and medium enterprises (SMEs) in Palembang. This study explains how the influence of market orientation and understanding of product quality by the owner or leader of the Songket UKM in Palembang City on the company's performance. The research sample amounted to 50 people consisting of elements of the owners and leaders of the Palembang songket UKM and that is from 25 Palembang UKM business units. Survey method with quantitative management data through statistical analysis test of the SPss IBM 25 application to measure the level of market orientation, product quality, supply chain management strategy on the performance of SMEs in Palembang. These results show that the Market orientation has a significant positive role on the performance of SME companies in the city of Palembang and it can provide an alternative solution in the form of information on awareness of the influence of the variables studied as owners or leaders of SMEs on market orientation, product quality , supply chain management strategies to improve the performance of songket SMEs in Palembang.